2021
DOI: 10.1021/acscatal.1c00014
|View full text |Cite
|
Sign up to set email alerts
|

Ureate Titanium Catalysts for Hydroaminoalkylation: Using Ligand Design to Increase Reactivity and Utility

Abstract: Hydroaminoalkylation describes the atom-economical catalytic synthesis of amines by forming new Csp3 –Csp3 bonds using readily available amine and alkene feedstocks. Herein, we describe an earth-abundant and cost-efficient titanium catalyst generated in situ using commercially available Ti­(NMe2)4 and a simple to synthesize urea proligand. This system demonstrates high TOFs for hydroaminoalkylation with unactivated substrates and features easy to use commercially available titanium amido precursors. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…While there are a few examples of late-transition-metal complexes with the aziridine binding motif, the vast majority of isolated examples contain hard Lewis acidic early transition metals with bonding motifs most consistent with the metallaaziridine formulation . The latter variant is particularly interesting because these complexes can be used as α-amino carbanion equivalents, as opposed to π-bound electrophiles, to access a variety of α-substituted nitrogen-containing molecules in stoichiometric or catalytic transformations involving unsaturated molecules. For example, metallaaziridine species are key intermediates in early-transition-metal-catalyzed hydroaminoalkylation reactions, where the α-C–H bond of an amine is added across an unsaturated C–C bond of an alkene or an alkyne , in a 100% atom-economical fashion (see Scheme b).…”
mentioning
confidence: 99%
“…While there are a few examples of late-transition-metal complexes with the aziridine binding motif, the vast majority of isolated examples contain hard Lewis acidic early transition metals with bonding motifs most consistent with the metallaaziridine formulation . The latter variant is particularly interesting because these complexes can be used as α-amino carbanion equivalents, as opposed to π-bound electrophiles, to access a variety of α-substituted nitrogen-containing molecules in stoichiometric or catalytic transformations involving unsaturated molecules. For example, metallaaziridine species are key intermediates in early-transition-metal-catalyzed hydroaminoalkylation reactions, where the α-C–H bond of an amine is added across an unsaturated C–C bond of an alkene or an alkyne , in a 100% atom-economical fashion (see Scheme b).…”
mentioning
confidence: 99%
“…Also, less toxic and less expensive early-transition metals (ETM) from groups 3, 4 and 5, including earth abundant metals like titanium can be used as catalysts. [22][23][24][25][26] In recent years this strategy has proven to be an efficient, thermally promoted reaction. However, like many other C-H functionalization reactions, this transformation often requires very high reaction temperatures of up to 180 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently showed that highly active tantalum and titanium ureate hydroaminoalkylation catalysts can be prepared in situ for the efficient alkylation of both aryl and alkyl N -methylated secondary amines. Although reactivity with N -heterocycles was not achieved, this earlier work showcased the tunable nature of ureate ligand salts to improve catalytic activity and enhance substrate scope. Here, we report a tantalum ureate catalyst for the rapid α-C–H alkylation of saturated N -heterocycles with activated and unactivated alkene coupling partners (Figure c).…”
Section: Introductionmentioning
confidence: 99%